2019
DOI: 10.1007/s12520-019-00889-2
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic evidence of strong reliance on animal foods and dietary heterogeneity among Early-Middle Neolithic communities of Iberia

Abstract: Stable carbon and nitrogen isotope research on past populations in the Iberian Neolithic has emphasized the Atlantic and Mediterranean coasts. This study provides the first isotopic insights into the diet and subsistence economy of Early and Middle Neolithic populations from open-air sites in interior north-central Iberia. We present bone collagen carbon (δ 13 C) and nitrogen (δ 15 N) isotope ratios for 44 humans and 33 animals recovered from six cemeteries of the Ebro valley and the northern Iberian Plateau. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Low correlation between δ 13 C diet protein and Δ bioapatite–collagen at El Japón is linked to protein sources of low trophic level in both the pooled male and female sample: plant foods or low trophic level animals. In contrast, strong correlations between δ 13 C whole diet and Δ bioapatite–collagen are observed in compared neolithic Iberians (Figure 5) where zooarchaeological evidence indicates high animal product consumption (Fernández‐Crespo et al, 2019). There, meat and animal byproducts likely provided a large share of both dietary protein and energy.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Low correlation between δ 13 C diet protein and Δ bioapatite–collagen at El Japón is linked to protein sources of low trophic level in both the pooled male and female sample: plant foods or low trophic level animals. In contrast, strong correlations between δ 13 C whole diet and Δ bioapatite–collagen are observed in compared neolithic Iberians (Figure 5) where zooarchaeological evidence indicates high animal product consumption (Fernández‐Crespo et al, 2019). There, meat and animal byproducts likely provided a large share of both dietary protein and energy.…”
Section: Discussionmentioning
confidence: 96%
“…Summary statistics and sources of faunal and botanical samples used as proxies are presented in Supplemental Tables 3–6. Human isotopic data: Cholula (Alcantara‐Russell, 2020), Campeche (Price et al, 2012), Ecatepec (Moreiras Reynaga et al, 2020), and Neolithic Iberia (Fernández‐Crespo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our estimates do not differ from the conclusions of other studies that explore the Neolithic diet in other parts of Europe. For example, using stable isotope analysis of human bone collagen, it was observed that the majority of the diet of Neolithic communities in England and Scotland have an animal origin 60 62 and considerable consumption of animal proteins was suggested in Neolithic Switzerland 63 , Germany 64 – 66 , Hungary 67 , north and central France 68 70 , Spain 71 , 72 , Greece 73 and Croatia 74 . Recently, animal products have been estimated to contribute more than 50% of the diet in Neolithic Malta, probably due to a high reliance on dairy 75 .…”
Section: Discussionmentioning
confidence: 99%
“…There is no 14 C date for this burial, but the context suggests a date in the Early Neolithic, probably ca. 4650-4400 cal BC (subphase Iii) (Fernández-Crespo, et al, 2019).…”
Section: mentioning
confidence: 99%